2017
DOI: 10.1136/bjophthalmol-2017-311384
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for late age-related macular degeneration in India

Abstract: Background/AimsThere are limited data from India on genetic variants influencing late age-related macular degeneration (AMD). We have previously reported associations from a population-based study in India (the India age-related eye disease study (INDEYE)) of early AMD and single nucleotide polymorphisms (SNPs) in ARMS2/HTRA1 and no association with CFH, C2 or CFB. Late AMD cases were too few for meaningful analyses. We aimed to investigate SNPs for late AMD through case enrichment and extend the loci for earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…The ABCA1 gene encodes the ABC transporter A1 (ABCA1), a cholesterol efflux pump in the cellular lipid removal pathway (Cavelier et al 2006;Liu & Tang 2012b) expressed in human retina and RPE (Tserentsoodol et al 2006;Duncan et al 2009;Zheng et al 2012 andStorti et al 2017). Although many authors have found an association between ABCA1 rs1883025 and AMD (Chen et al 2010b;Wang et al 2016 andRajendran et al 2018), in the present study no statistical differences were found in the Northern Spanish cohort, in agreement with other reports in Caucasian (Neale et al 2010;Fauser et al 2011 andPeter et al 2011) or Asian populations (Tian et al 2012;Zhang et al 2013 andLi et al 2014). On the other hand, the ABCA4 encodes a protein implicated in the clearance of all-trans-retinal aldehyde from photoreceptors completing the photo-cycle (Papermaster et al 1982;Azarian &Travis 1997 andMolday et al 2000), in which mutations are responsible for Stargardt macular dystrophy, related retinal degenerative diseases and may predispose to AMD (Allikmets 2000;Beharry et al 2004;Ratnapriya & Chew 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ABCA1 gene encodes the ABC transporter A1 (ABCA1), a cholesterol efflux pump in the cellular lipid removal pathway (Cavelier et al 2006;Liu & Tang 2012b) expressed in human retina and RPE (Tserentsoodol et al 2006;Duncan et al 2009;Zheng et al 2012 andStorti et al 2017). Although many authors have found an association between ABCA1 rs1883025 and AMD (Chen et al 2010b;Wang et al 2016 andRajendran et al 2018), in the present study no statistical differences were found in the Northern Spanish cohort, in agreement with other reports in Caucasian (Neale et al 2010;Fauser et al 2011 andPeter et al 2011) or Asian populations (Tian et al 2012;Zhang et al 2013 andLi et al 2014). On the other hand, the ABCA4 encodes a protein implicated in the clearance of all-trans-retinal aldehyde from photoreceptors completing the photo-cycle (Papermaster et al 1982;Azarian &Travis 1997 andMolday et al 2000), in which mutations are responsible for Stargardt macular dystrophy, related retinal degenerative diseases and may predispose to AMD (Allikmets 2000;Beharry et al 2004;Ratnapriya & Chew 2013).…”
Section: Discussionsupporting
confidence: 91%
“…This analysis confirmed that the SNP rs10468017 was independently associated with the prevalence of AMD. The SNP rs10468017, placed in the promoter region, has been previously reported to be associated with protection of late AMD (allele T) in different Caucasian populations (Reynolds et al 2010;Neale et al 2010;Seddon et al 2010;Yu et al 2011a,b;Peter et al 2011;Cipriani et al 2012;Yu et al 2012;and Liutkeviciene et al 2019), but not associated in European ancestry (Sobrin et al 2011), Chinese (Tian et al 2012 andZhang et al 2013) or Indian populations (Rajendran et al 2018). Although our results were consistent with the protection of the allele T in the dry form of AMD, the association was not significant after Bonferroni correction.…”
Section: Discussioncontrasting
confidence: 47%
“…There have been several studies from Asian population available for direct comparison. 15,[30][31][32] ARMS2 A69S gene polymorphisms have been consistently associated with nAMD in Malaysian, 33 Chinese Singaporean, 31 Thai, 30 Chinese, 34,35 Japanese, 36,37 Korean, 38 Indian, 32 and European populations. 39 It has also been reported that ARMS2 A69S has stronger associations with nAMD than CFH Y402H, 40 which is comparable to our study findings.…”
Section: Discussionmentioning
confidence: 98%
“…Also, a Chinese study confirmed the importance of VEGF on AMD [76]. An Indian study found associations with neovascular AMD for an SNP near VEGFA (rs4711751) (OR = 0.64, 95% CI 0.54 to 0.77, P = 10 −3 ) [77]. An Italian study involved a cohort of 1976 subjects, including 976 patients affected with exudative AMD and 1000 control subjects.…”
Section: Discussionmentioning
confidence: 98%